Comparison Between The Effect of Clove, Filter and Biomass Cigarette Smoke to The Lung Function of COPD Patients at Harum Melati Pringsewu Clinic Lampung Province, Period January 2013-January 2020 - Retno Ariza S Soemarwoto; Hetti Rusmini; Fransisca Sinaga; Agus Dwi Susanto; Arif Widiyantoro (Jurnal Respirologi Indonesia, 2021)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a common disease characterized by respiratory symptoms and limited air flow associated with the airways and/or alveolar abnormalities triggered by a significant effect on substances or gases. COPD is the leading of death cause in the world. COPD can be caused by cigarette smoke and biomass. Method: This research is aquantitative method with descriptive analytic and retrospective approach. The samples were 203 COPD patients taken from medical records January 2013-January 2020 at Harum Melati Pringsewu Clinic Lampung Province with statistical test use Analysis Varians (ANOVA) technique. Results: From the characteristics based on type of COPD smoke exposure were clove smokers 127 people (62.6%), filter smokers 3 people (1.5%) and biomass users 73 people (36.0%). The mean lung function COPD patients based on type of smoke exposure were 127 people with clove smokers with average lung function value 55.03%, the lowest value 12.20% and the highest 121.50%. Filter smokers of 3 people with average lung function value 75.07%, the lowest value was 67.00% and the highest 81.41%. Biomass users 73 people with average lung function value 56.91%, the lowest value 19.50% and the highest 149.13%. Comparison the effect clove cigarettes smoke, filter cigarettes and biomass on the pulmonary function of COPD patients obtained P=0.319. Conclusion: There is a decrease lung function in clove smokers, filter smokers and biomass users in COPD patients but not statistically significant difference.